The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.4049/jimmunol.1501249
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1–Mediated BAFF Secretion in Macrophages Does Not Require Endosomal TLRs, Type-I IFN, and Nef, but Depends on the Cellular Phenotype Status

Abstract: HIV-1 infection is characterized by persistent viral replication, chronic immune activation, and CD4+ T cell depletion. Moreover, several immune dysfunctions are observed in cells that are not targeted by the virus, such as B cells. Some B cell abnormalities include hypergammaglobulinemia, nonspecific B cell activation, class switching, increased cell turnover, breakage of tolerance, and a loss of the capacity to generate and maintain memory. Several cytokines and growth factors that are increased in the serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 93 publications
(102 reference statements)
1
5
0
Order By: Relevance
“…This virus-mediated effect is essentially independent on replication since it was observed with AT2-inactivated virus. Extending our results, Gomez et al recently showed that HIV-1 does not induce BAFF expression in monocyte-derived macrophages displaying a M1 phenotype ( 92 ). Unexpectedly, our findings showed that mBAFF was expressed by a majority of pDC in healthy individuals, an expression that strongly decreased in patients with primary HIV infection.…”
Section: Evidence For Soluble and Membrane Baff Overexpression Duringsupporting
confidence: 87%
“…This virus-mediated effect is essentially independent on replication since it was observed with AT2-inactivated virus. Extending our results, Gomez et al recently showed that HIV-1 does not induce BAFF expression in monocyte-derived macrophages displaying a M1 phenotype ( 92 ). Unexpectedly, our findings showed that mBAFF was expressed by a majority of pDC in healthy individuals, an expression that strongly decreased in patients with primary HIV infection.…”
Section: Evidence For Soluble and Membrane Baff Overexpression Duringsupporting
confidence: 87%
“…M1 typically secrete pro-inflammatory cytokines (TNFα, IL-6), while M2 mainly promote Th2 responses, immunosuppression, and tumor promotion. [31, 36] It is interesting to note that many of the cytokines or chemokines associated with AIDS-NHL risk are typically produced by M1 polarized macrophages, including IP10, TNFα, IL18, IL6 and BAFF, [31, 32, 36] which may be reflecting microbial translocation and activation of macrophages by LPS. Some notable M2 markers, including CCL17 and CD163, [31, 36] were also associated with AIDS-NHL risk, possibly reflecting the presence of tumor-associated, tumor growth-promoting, macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments were performed with human peripheral blood monocytes that were differentiated into uncommitted/nonpolarized MØ (M0 phenotype). This information is of prime importance since the activation status of human MØ has been reported to affect HIV-1 replication 16 . Our technical procedure is based on replication-competent HIV-1 particles coding for the murine HSA cell surface molecule.…”
Section: Discussionmentioning
confidence: 99%